2018
DOI: 10.1002/bmc.4160
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and metabolic profile of Xian‐Ling‐Gu‐Bao capsule, a traditional Chinese medicine prescription, with rat intestinal microflora by ultra‐performance liquid chromatography coupled with quadrupole time‐of‐flight tandem mass spectrometry analysis

Abstract: Xian-Ling-Gu-Bao capsule (XLGB), a well-known traditional Chinese medicine prescription, has been used for the prevention and treatment of osteoporosis. The safety and efficacy of XLGB have been confirmed based on the principle of evidence-based medicine. XLGB is usually administered orally, after which its multiple components are brought into contact with intestinal microflora in the alimentary tract and biotransformed. However, investigations on the comprehensive metabolic profile of XLGB are absent. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In TCM preparation, the phytochemicals exhibit low oral bioavailability, in particular glycosides are possessing poor membrane permeability [ 40 ]. Moreover, these glycosides are inevitable to be transformed by microbial hydrolysis in intestinal before their absorption to the gut [ 41 ]. Herein, the role of β-D-glucosidase in food and/or pharmaceutical bioprocessing could promote aglycone entering blood circulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In TCM preparation, the phytochemicals exhibit low oral bioavailability, in particular glycosides are possessing poor membrane permeability [ 40 ]. Moreover, these glycosides are inevitable to be transformed by microbial hydrolysis in intestinal before their absorption to the gut [ 41 ]. Herein, the role of β-D-glucosidase in food and/or pharmaceutical bioprocessing could promote aglycone entering blood circulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In TCM preparation, the phytochemicals exhibit low oral bioavailability, in particular, glycosides are possessing poor membrane permeability [36]. Moreover, these glycosides are inevitable to be transformed by microbial hydrolysis in intestinal before their absorption to the gut [37]. Herein, the role of β-D-glucosidase in food and/or pharmaceutical bioprocessing could promote aglycone entering blood circulation [38].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that cleavage and deglycosylation of glycosylated groups were the main metabolic pathways of various glycosides. Notably, amino acid binding was first found in the metabolism of pentene-flavonoid glycosides in the intestinal flora of rats ( 117 ).…”
Section: Metabolomics For the Development Of Op Therapeuticsmentioning
confidence: 99%